Relationship of Health Belief Model with Medication Adherence in RW 11, Bangetayu Kulon Village, Semarang - Novita, Mutiara Putri; Kusuma, Alim Wida Titra; Fajar, Bintang; Darmawan, Bagus Rifqi; Dewi, Hannia Efitra; Maharani, Yulianti Dewi; Ratnawati, Ratnawati (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Hypertension cases in Indonesia are on the rise annually. Identifying risk factors is crucial for prevention. Risk factors include non-modifiable elements and modifiable ones. The Health Belief Model (HBM) is widely used to understand patient adherence to antihypertensive treatment adherence. Objective: This study aimed to pinpoint key patient adherence to antihypertensive treatment in RW 11, Bangetayu Kulon Village, Semarang. Methods: A cross-sectional quantitative design. Independent variables included perceived susceptibility, severity, benefits, barriers, self-efficacy, and cues to action, while the dependent variable was adherence to antihypertensive medication. The sample comprised 33 hypertensive patients selected through purposive sampling. Data collection involved a validated questionnaire administered via interviews. Statistical analysis was conducted using SPSS version 27, with chi-square for bivariate analyses, and logistic regression for multivariate analysis. Results: Bivariate analysis indicated that perceived susceptibility, benefits, severity, and self-efficacy significantly correlated with treatment adherence. Multivariate analysis revealed that perceived severity and self-efficacy were the strongest predictors of adherence, with self-efficacy being the most dominant factor (PR 33.67, 95% CI 2.937–385.989, p = 0.005). Conclusion: The Health Belief Model effectively predicts medication adherence among hypertensive patients. Interventions aimed at improving self-efficacy and emphasizing perceived severity of hypertension could enhance patient adherence to treatment.